PEMANFAATAN MEDIA CYBER PR JELANG ASEAN COMMUNITY - Dasrun Hidayat; Anisti Anisti (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2015)
Abstract: Context problems studied in this paper about the framework of public relations strategy with the use of cyber media PR company in Indonesia through the pillar ahead of the Asean Economic Community. The issue was raised because of the presence of new media or new media in recent years greatly helped the workings of the PR company in an effort to improve the effectiveness of the company's work. However, the use of cyber media as a working tool is considered less than optimal because of the level of understanding of the working methods of the technology-based media. This paper uses the method of writing a literature review. This study is expected to provide an understanding of PR companies to use contemporary media or new media in this regard cyber media PR includes all programs that can be used by technology or e-PR. Awareness of PR companies is very important, as the Indonesian company strategy ahead of the ASEAN Community. The three main pillars of the establishment of the ASEAN Community, namely (1) the ASEAN Political and Security Community (2) and the Asean Economic Community (3) Social and Cultural Community ASEAN. In this scientific paper the authors focus on the ASEAN Economic Community through the use of cyber media Tekonologi PR companies. Asean Community will open up opportunities for ASEAN countries to compete in the interstate without limit again lies the region. This means that each ASEAN country has a great opportunity, and equal opportunities to develop the economy of the ASEAN countries through two key words that excellent service and quality products. Keywords: business strategy, cyber media, asean pillar of community Abstrak: Konteks masalah yang dikaji dalam paper ini mengenai strategi kerja public relation dengan pemanfaatan media cyber PR perusahaan di Indonesia melalui pilar ekonomi jelang Asean Community. Masalah ini diangkat karena hadirnya media baru atau new media beberapa tahun terakhir ini sangat membantu cara kerja PR perusahaan dalam upaya meningkatkan efektifitas kerja perusahaan. Akan tetapi, pemanfaatan media cyber sebagai alat kerja tersebut dirasa kurang optimal karena tingkat pemahaman tentang metode kerja melalui media berbasis teknologi tersebut. Penulisan paper ini menggunakan metode kajian literatur. Kajian ini diharapkan memberikan pemahaman PR perusahaan terhadap pemanfaatan media kontemporer atau media baru dalam hal ini media cyber PR meliputi semua program yang dapat digunakan melalui teknologi atau e-PR. Kesadaran kerja PR perusahaan ini sangat penting, sebagai strategi perusahaan Indonesia jelang Asean Community. Tiga pilar utama terbentuknya Asean Community yaitu (1) Komunitas Politik dan Keamanan Asean, (2) Komunitas Ekonomi Asean dan (3) Komunitas Sosial dan Budaya Asean. Pada paper ilmiah ini penulis fokus pada Komunitas Ekonomi Asean melalui pemanfaatan tekonologi media cyber PR perusahaan. Asean Community akan membuka kesempatan bagi negara-negara Asean untuk bersaing antar negara tanpa di batasi lagi letak wilayah. Artinya bahwa setiap negara Asean memiliki kesempatan yang besar dan peluang yang sama untuk mengembangkan ekonomi antar negara Asean melalui dua kata kunci yaitu layanan prima dan produk berkualitas.Kata Kunci: strategi kerja, cyber media, pilar asean community